Active and inactive components of the streamwise velocity in wall-bounded turbulence. (5th March 2021) - Deshpande, Rahul; Monty, Jason P.; Marusic, Ivan
Abstract: Abstract : Townsend ( J. Fluid Mech., vol. 11, issue 1, 1961, pp. 97–120) introduced the concept of active and inactive motions for wall-bounded turbulent flows, where the active motions are solely responsible for producing the Reynolds shear stress, the key momentum transport term in these flows. While the wall-normal component of velocity is associated exclusively with the active motions, the wall-parallel components of velocity are associated with both active and inactive motions. In this paper, we propose a method to segregate the active and inactive components of the two-dimensional (2-D) energy spectrum of the streamwise velocity, thereby allowing us to test the self-similarity characteristics of the former which are central to theoretical models for wall turbulence. The approach is based on analysing datasets comprising two-point streamwise velocity signals coupled with a spectral linear stochastic estimation based procedure. The data considered span a friction Reynolds number range $Re_{τ }\sim {O}$ ( $10^3$ ) – ${O}$ ( $10^4$ ). The procedure linearly decomposes the full 2-D spectrum ( ${\varPhi }$ ) into two components, ${\varPhi }_{ia}$ and ${\varPhi }_{a}$, comprising contributions predominantly from the inactive and active motions, respectively. This is confirmed by ${\varPhi }_{a}$ exhibiting wall scaling, for both streamwise and spanwise wavelengths, corresponding well with the Reynolds shear stress cospectra reported in the literature. Both ${\varPhi }_{a}$ and ${\varPhi }_{ia}$ are found to depict prominent self-similar characteristics in the inertially dominated region close to the wall, suggestive of contributions from Townsend's attached eddies. Inactive contributions from the attached eddies reveal pure $k^{-1}$ -scaling for the associated one-dimensional spectra (where $k$ is the streamwise/spanwise wavenumber), lending empirical support to the attached eddy model of Perry & Chong ( J. Fluid Mech., vol. 119, 1982, pp. 173–217).